Water Quality of the Mangetan Canal River of Keraton Village Plankton Diversity Index and Chemcial-Physical Parameters - Yulianto, Mochammad Ricky; Purnomo, Tarzan (LenteraBio : Berkala Ilmiah Biologi, 2023)
The Mangetan River Kanal is a tributary of the Brantas river which flows through the Keraton Village. This river has the potential to experience pollution because this river is located by the industrial sector, the agricultural sector, and the household sector. The purpose of this study was to determine water quality through the plankton diversity index and chemical-physical parameters in the Mangetan Kanal river. Sampling was carried out at 5 research station points with 3 repetitions for each station. Identification of plankton was carried out at the Ecology Laboratory, Department of Biology. while the physico-chemical parameters were tested in-situ in the field. The calculation of the plankton diversity index uses the Shannon-Wierner diversity index formula. The value of the plankton diversity index and the results of water quality measurements were analyzed descriptively. The dominating plankton is the Synedra ulna species. The highest diversity index was obtained at station 4 with a value of 2.42 and the smallest was obtained at station 3 of 1.91, the value was included in the moderate category and experienced light pollution. The abundance parameter ranged from 17.33-45.33Ind/L, this value was in the medium category and explains the Mangetan Kanal River as an oligotrophic river.